An analytical method for adjusting dead load allocation between side and central cables in a cable-stayed bridge with three cable planes. (February 2023) - Zhang, Wen-ming; Zou, Han-xu; Chen, Jie; Chang, Jia-qi
Abstract: Mechanical performance of cable-stayed bridges, especially those with super-wide main beams, can be significantly improved by adopting the three cable planes' scheme. However, broad application prospects of the novel bridge scheme require a proper adjustment of the ratio of the main beam's dead load allocated to the side and central cables. Otherwise, the central cables will bear an excessive dead load, deteriorating the overall bridge appearance and torsional stiffness. To this end, a simple analytical method was proposed for dead load allocation, reducing the share of the main beam's dead load borne by the central cable and re-allocating it to the side and central cables in any ratio by adjusting the unstressed lengths of the stay cables. This method takes full advantage of the convenience of adjusting the unstressed lengths of the stay cables and involves calculating the stay cables based on the catenary theory, which ensures high calculation accuracy. The proposed method first converts the spatial model of cable-stayed bridges with three cable planes into a planar model, employing the principle of virtual work to determine the elevation differences between the two anchor points of the three stay cables. Then, the unstressed lengths of stay cables are calculated based on the catenary theory. Finally, the proposed algorithm's feasibility is proved by applying the finite element method to a floating-type cable-stayed bridge with three cable planes with a main span of 1120 m and a bridge deck width of 75 m.